2023
DOI: 10.3390/molecules28093822
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase Inhibitors from Two Mangrove-Derived Actinomycetes

Abstract: α-Glucosidase (AGS) inhibitors have been regarded as an ideal target for the management of type 2 diabetes mellitus (T2DM) since they can maintain an acceptable blood glucose level by delaying the digestion of carbohydrates and diminishing the absorption of monosaccharides. In the process of our endeavor in mining AGS inhibitors from natural sources, the culture broth of two mangrove-derived actinomycetes Streptomyces sp. WHUA03267 and Streptomyces sp. WHUA03072 exhibited an apparent inhibitory activity agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Compound 35 exhibited enzyme inhibition against α -glucosidase (AGS) with an IC 50 value of 164.5 ± 15.5 µM, stronger than that of the positive control acarbose (IC 50 = 422.3 ± 8.44 µM). In addition, 35 showed no cytotoxicity to the human normal hepatocyte (LO2) cells, suggesting its safety to be developed into hypoglycemic agent [ 58 ]. Compound 36 showed antibacterial activity against Bacillus cereus and Proteus vulgaris with MIC values of 1.56 and 3.13 µM (the MIC of positive control ciprofloxacin was 0.78 and 0.20 µM) [ 59 ].…”
Section: Othersmentioning
confidence: 99%
“…Compound 35 exhibited enzyme inhibition against α -glucosidase (AGS) with an IC 50 value of 164.5 ± 15.5 µM, stronger than that of the positive control acarbose (IC 50 = 422.3 ± 8.44 µM). In addition, 35 showed no cytotoxicity to the human normal hepatocyte (LO2) cells, suggesting its safety to be developed into hypoglycemic agent [ 58 ]. Compound 36 showed antibacterial activity against Bacillus cereus and Proteus vulgaris with MIC values of 1.56 and 3.13 µM (the MIC of positive control ciprofloxacin was 0.78 and 0.20 µM) [ 59 ].…”
Section: Othersmentioning
confidence: 99%
“…geldanus var. nova [214], the ansamycin antibiotic geldanamycin (38) (Figure 4) is commonly described in marine strains of Streptomyces [215][216][217][218]. The pivotal work of Whitesell and Neckers demonstrated that 38 inhibited the formation of a v-Src-HSP90 complex through binding to the ATP-binding site in the N-terminal domain of HSP90 [219,220].…”
Section: Polyketidesmentioning
confidence: 99%
“…α-glucosidase inhibitors have been identified as a viable option for managing type 2 diabetes mellitus due to their ability to slow carbohydrate digestion and decrease the absorption of monosaccharides. This is due to their ability to maintain a stable blood glucose level within tolerable limits . Therefore, one of the most important ways to stop diabetes from developing is to reduce postprandial hyperglycemia. , α-Glucosidase is found in a wide range of organisms .…”
Section: Introuctionmentioning
confidence: 99%
“…This is due to their ability to maintain a stable blood glucose level within tolerable limits. 2 Therefore, one of the most important ways to stop diabetes from developing is to reduce postprandial hyperglycemia. 3 , 4 α-Glucosidase is found in a wide range of organisms.…”
Section: Introuctionmentioning
confidence: 99%